OSTEOARTHRITIS AND HIGH BLOOD PRESSURE: MECHANISMS FOR REALIZATION OF THE COMBINED COURCE - Pasiyeshvili, L. M. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
In patients with high blood pressure were identified low levels of calcium in the blood and elevated levels of calcium in the urine. These changes were more pronounced in combination with osteoarthritis. These changes may be a negative factor for the combined cource of these diseases and contribute to the progression. This combination is the foundation for replacement therapy.